Effects of Dietary Manganese Proteinate or Chromium Picolinate Supplementation on Plasma Insulin, Glucagon, Glucose and Serum Lipids in Broiler Chickens Reared Under Thermoneutral or Heat Stress Conditions. - Sands, J.S.; Smith, M.O. (International Journal of Poultry Science, 2002)
A study was conducted to investigate the effects of supplemental chromium picolinate (CrPic) or manganese proteinate (MnPro) on heat-distressed broiler chickens. In a completely randomized design, diets were supplemented with either 200 or 400 ug Cr/kg as CrPic or 0, 60 and 240 mg Mn/kg as MnPro and fed to broilers under heat stress (HS) or thermoneutral (TN) conditions. Commercial broilers were reared in brooder pens and fed the experimental diets from Day 1 to 21 and then assigned the same dietary treatments in one of two environmentally controlled chambers. One chamber was maintained at 23.9 °C, whereas birds in the second chamber were exposed to 8-h of 23.9 °C, 4-h of 23.9 to 35 °C, 4-h of 35 °C and 8-h of 35 to 23.9 °C. At 9 wks, plasma concentration of insulin (I) was lower (p0.05) by dietary treatment regimen. Heat stress lowered insulin (p